Agonist efficacy at the β2AR is driven by the faster association rate of the Gs protein - Harwood, Clare R.; Sykes, David A.; Redfern-Nichols, Theo; Underwood, Owen; Nicholson, Colin; Khoshgrudi, Armin N.; Koers, Eline J.; Ladds, Graham; Briddon, Stephen J.; Veprintsev, Dmitry B. (Frontiers in Pharmacology, 2025)
IntroductionThe β2-adrenoceptor (β2AR) is a class A G protein-coupled receptor (GPCR). It is therapeutically relevant in asthma and chronic obstructive pulmonary disease (COPD), where β2AR agonists relieve bronchoconstriction. The β2AR is a prototypical GPCR for structural and biophysical studies. However, the molecular basis of agonist efficacy at the β2AR is not understood. We hypothesised that the kinetics of GPCR–G protein interactions could play a role in determining ligand efficacy. By studying a range of agonists with varying efficacy, we examined the relationship between ligand-induced mini-Gs binding to the β2AR and ligand efficacy, along with the ability of individual ligands to activate the G protein in cells.MethodsWe used NanoBRET technology to measure ligand-induced binding of purified Venus-mini-Gs to β2AR-nLuc in membrane preparations under both equilibrium and kinetic conditions. In addition, we examined the ability of these β2AR agonists to activate the heterotrimeric Gs protein, measured using the Gs-CASE protein biosensor in living cells. This assay detects a reduction in NanoBRET between the nano-luciferase (nLuc) donor on the Gα subunit and Venus acceptor on the Gγ upon Gs protein activation.ResultsThe 12 β2AR agonists under study revealed a broad range of ligand potency and efficacy values in the cellular Gs-CASE assays. Kinetic characterisation of mini-Gs binding to the agonist β2AR complex revealed a strong correlation between ligand efficacy values (Emax) and mini-Gs affinity (Kd) and its association rate (kon). In contrast, there was no correlation between ligand efficacy and reported ligand dissociation rates (or residence times).ConclusionThe association rate (kon) of the G protein to the agonist β2AR complex is directly correlated with ligand efficacy. These data support a model in which higher-efficacy agonists induce the β2AR to adopt a conformation that is more likely to recruit G protein. Conversely, these data did not support the role of agonist binding kinetics in determining the molecular basis of efficacy.